Transcranial direct current simulation as an adjunctive treatment for treatment-resistant depression in hospitalized patients: A feasibility study protocol - John W. Li; Caili Ren; Vanessa K. Pazdernik; Simon Kung; Michael R. Basso; Paul E. Croarkin; Bina Aaron; Amanda M. Anderson; Courtney A. Caves; Misty N. Hemm; Ashley L. Holland; Charlie R. Hoth; et al. (PLoS ONE, 2025)
Transcranial direct current stimulation (tDCS) is clinically effective in treating treatment-resistant depression (TRD), as measured by response, symptom improvement, and disease remission. However, the feasibility and underlying mechanism of tDCS treatment in individuals with TRD during acute psychiatric hospitalization remain poorly characterized. This paper outlines the protocol that aims to investigate the feasibility of implementing a 5-day tDCS treatment in hospitalized patients with TRD and secondarily explore the effects on depression and cognition, and neurophysiological mechanisms underlying tDCS. Current study will enroll ten participants who are diagnosed with TRD and are hospitalized in psychiatric units. Participants will receive a 5-day tDCS treatment protocol, with each treatment session lasting for 30 minutes, delivered twice daily, for a total of 10 stimulations over 5 days. The primary outcomes are the feasibility, acceptability, and tolerability of administering a 5-day tDCS treatment protocol in acutely hospitalized TRD patients. Exploratory outcomes pre- and post-tDCS include measures of depression (Montgomery-Asberg Depression Rating Scale (MADRS)) and cognition (Stroop Test, Revised Hopkins Verbal Learning Test (HVLT-R), Digital Symbol Coding Test (DSCT)), EEG changes in peak alpha frequency (PAF), and cerebral hemodynamic changes by functional near-infrared spectroscopy (fNIRS). This protocol would provide feasibility evidence for tDCS as an add-on to the standard of care treatment of TRD in hospitalized patients. Upon completion of the protocol, the preliminary effects of the 5-day tDCS treatment protocol regarding depression and cognitive symptoms and its neurophysiological mechanisms will be identified to guide the design and delivery of a randomized controlled study. Trial registration: National Institute of Health Clinicaltrials.gov (NCT06236711) and protocol ID: 23–003274.